Outcome predictors of intravenous thrombolytic therapy in acute ischemic stroke patients: an Egyptian center experiences - Mohamed A. Tork; Hany M. Aref; Hala M. El-Khawas; Mohamed F. Khalil; Ahmed ElSadek (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2020)
Abstract Background Intravenous thrombolytic therapy remains the guideline-recommended treatment to improve outcomes after acute ischemic stroke. However, the functional outcome among patients with acute ischemic stroke after receiving intravenous thrombolytic therapy is influenced by huge variety of factors, and this was the aim of our study to evaluate the outcome predictors of intravenous thrombolytic therapy in a sample of Egyptian patients with acute ischemic stroke. Methods We enrolled 183 acute ischemic stroke patients who were treated with intravenous recombinant tissue plasminogen activator (IV rtPA) according to the last updated guidelines of American Heart Association and American Stroke Association (AHA/ASA) from February 2018 to February 2020; however, only 150 patients of them completed our study plan till the end. Data of study variables were collected, analyzed statistically and correlated with the functional outcome 3 months after receiving IV rtPA using the modified Rankin Scale (mRS). Results Good functional outcome was seen in 98 (65.3%) patients and poor functional outcome was seen in 52 (34.7%) patients. Multivariate analysis of the study variables was done to detect the significant independent predictors of the functional outcome. Atrial fibrillation (AF) (P value < 0.001*OR 6.28* (95% C.I)), hypertension (P value 0.001*OR 3.65*(95% C.I)), diabetes mellitus (DM) (P value 0.009*OR 2.805*(95% C.I)), increased National Institute of Health Stroke Scale (NIHSS) score 24 h after receiving IV rtPA (P value 0.003* OR 8.039* (95% C.I)), increased pulsatility index (PI) value in cerebral vessels at the same side of stroke lesion (P value 0.038* OR 42.48*(95% C.I)) were the significant independent predictors of poor functional outcome. On the other hand decreased NIHSS score 24 h after receiving IV rtPA (P value 0.003* OR 0.124*(95% C.I)), Normal value of PI in cerebral vessels at the same side of stroke lesion (P value 0.038* OR 42.48*(95% C.I)) were the significant independent predictors of good functional outcome. Conclusion Intravenous thrombolytic therapy improves the functional outcome of acute ischemic stroke patients. Also, AF, hypertension, DM, NIHSS 24 h after receiving IV rtPA and PI could be used as independent predictors of the functional outcome.